Single-cell to pre-clinical evaluation of Trem2, Folr2, and Slc7a7 as macrophage-associated biomarkers for atherosclerosis - Örd, Tiit; Palani, Senthil; Giroud Gerbetant, Judith; Bodoy, Susanna; Lönnberg, Tapio; Niskanen, Henri; Ravindran, Aarthi; Holappa, Lari; Chemaly, Melody; Taipale, Mari; Õunap, Kadri; Haikonen, Retu; et al. (Oxford University Press (OUP), 2026)
Aims
Atherosclerosis is a major global health challenge, with limited diagnostic and therapeutic options. Macrophages drive disease progression, but their tissue-specific phenotypes and functions remain poorly defined. This study aims to elucidate macrophage-driven mechanisms by characterizing their functional diversity across key metabolic and vascular tissues.
Methods and Results
We used single-cell RNA sequencing (scRNA-seq) and Translating Ribosome Affinity Purification sequencing (TRAP-seq) to profile macrophage-specific gene programs in a mouse model of atherosclerosis across the aorta, adipose tissue, and liver. Our data highlights tissue-specific macrophage gene programs and identifies markers that are shared across mouse and human plaques. First, we identified soluble Trem2 as a potential circulating biomarker for differentiating between asymptomatic and symptomatic individuals. Secondly, we leveraged the pronounced expression of Folr2 and Slc7a7 to explore the potential of folate and glutamine as PET tracers for disease burden assessment through in vivo positron emission tomography (PET) imaging. Finally, we show that knockout of Slc7a7 inhibits acetylated low-density lipoprotein (AcLDL) uptake and dampens the gene signature linked to lipid-associated macrophages. This suggests that glutamine signaling may play a critical role in foam cell formation, a key event in atherosclerosis.
Conclusions
Our findings provide novel insights into macrophage-specific gene programs during atherosclerosis progression and identify a set of promising biomarkers that can serve as a resource for future studies. These findings could significantly contribute to improving the diagnosis, monitoring, and treatment of atherosclerosis.